Validating Bachelorhood - Slawinski, Scott (Studies in American Popular History and Culture, 2005)
This book explores images of single and married men in C.B. Brown's Monthly Magazine and concludes that Brown used his periodical as a vehicle for validating bachelorhood as a viable alternative form of masculinity.